Pergeseran Jenis Gulma Akibat Perlakuan Bahan Organik pada Lahan Kering Bekas Tanaman Jagung (Zea maysL.) - Fitriana, Maria; Parto, Yakup; Munandar, ,; Budianta, Dedik (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
The objective of this study was to examine shifting of weeds species on upland previously planted with corn and treated with several organic matters. The experiment was conducted from August 2010 until January 2011, at Bakung Indralaya South Sumatera. Randomized complete block design was used with 7 treatments and 3 replications. The treatments were types of organic matters applied, consisted of planted Mucuna bracteata, planted Vigna unguiculata, compost of M. bracteata, compost of corn stalk, buried corn stalk, cow manure, and fallow. The plot size was 5 m x 20 m with 5 sampling plots. The sampling plot size was 1 m x 1 m each. The results showed that there were change in weeds composition after organic matter treatments. There were 18 species of weeds before treatments which were dominated by Panicum maximum, Eleusine indica, and Borreria laevis. After the organic matter treatments there were 22 weeds species, which classified into 17 genus and 11 families, floristically. The main weeds were Richardia brasiliensis, Borreria alata, and Eleusine indica. The weeds diversity index was less to medium with the point of 1.33 to 1.85. The community coefficient between before and after organic matter treatment was < 30% , while the average of communities coefficient between organic matter treatments above 75%.Keywords: diversity, organic matter, shifting species, weeds